Mobile Application Development Strategies (International Journal of Engineering and Computer Science, 2017)
Mobile application development has entered new stage largely driven by advent of highly influential iOS, android etc. bases smartphones and tablet devices. In sales, smart mobile devices are outpacing conventional computer clients. While mobile app development is still primarily province of customer applications, time has come that enterprise development teams need to prepare their applications to run on intelligent mobile devices. There are few major categories of mobile app delivery available today. These are: Native type, running directly on device, web based types, employing device’s web browser; a hybrid of native and web based types. Each approach is suitable to work in different environments and also each has some pros and cons in comparison with others. There are many factors that play a part in deciding mobile development strategy, such as development skills, required device functionality, the importance of security, offline capability, interoperability, multiplatform support, deployment method etc. that must be taken into account.